A Preliminary Study on Prevalence of Non-Communicable Diseases and their Association with Physical activity among the Urban Geriatric Population - Majumder, Sneha; Arlappa, Nimmathota; Palla, Suryanarayana; Vadakattu, Sai Santhosh (Indian Journal of Community Health, 2019)
Background: India is experiencing a rapid health transition with a rising burden of Non-Communicable Diseases (NCDs) and inappropriate lifestyle is the most remarkable risk factor associated to NCDs. Aims & Objectives: To assess the prevalence of NCDs and their association with physical activity among urban elderly. Material and methods: A community based cross-sectional study was conducted among 112 geriatric population (?60 years) in cities of Hyderabad and Secunderabad. The data on medical history, lifestyle, diet and physical activity was obtained using a pre-tested questionnaire. Anthropometric measurements such as weight, height and waist circumference were measured. Intravenous blood samples were collected to estimate the biochemical parameters. Result: About 64.3 % of elderly have been practicing physical activity i.e. predominantly walking, while 35.7% were sedentary. The prevalence of hypertension (87.5%), diabetes (65.3%), central obesity (77.8%) and metabolic syndrome (59.7%) was higher among walkers as compared to non-walkers and the prevalence of metabolic syndrome was significantly (p<0.005) high among the elderly suffering from Cardio Vascular Diseases (CVDs). Conclusion: In general, the prevalence of non-communicable diseases was high among urban geriatric population. Therefore, primordial and primary preventive measures should be adopted during adolescence and early adulthood for the prevention and control of NCDs.